Beban Ganda yang dialami Perempuan Kulit Hitam dalam Dua Novel Toni Morrison 'A Mercy' dan 'Home' - Nurul Laili Nadhifah; Arcci Tusita; Sri Herminingrum (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2017)
The double burden experienced by black women is not only done by white people as colonizer, but also black men. Because the double minority they experience, Black women receive worse treatment than white female, since they are not seen as fully human. This research uses two novels by Tony Morrison; Home (2012) andA Mercy (2008) focusing on the double burden and its impacts experienced by black female main characters as the result of colonialism. The burdens experienced by black women are mainly about racism and sexism either done by white people or black men. Centered on the character of Cee in Home and Florens in A Mercy, this research applies Poscolonialism approach and Black feminism theory. The result of this research is expected to be a model on analyzing a novel written by African-American author for novel analysis subject and reference for other researches related to black feminism and poscolonialism.